Exercise experiences in patients with metastatic lung cancer: A qualitative approach - Chang, Pi-Hua; Lin, Ching-Rong; Lee, Yun-Hsiang; Liu, Yi-Lin; Chang, Gee-Chen; Hoogland, Aasha I.; Lai, Yeur-Hur (PloS one, 2020)
Patients with metastatic lung cancer can have severe cancer-related symptoms and treatment-induced side effects. Exercise is beneficial for patients with metastatic lung cancer; however, little information is available on guiding patients how to perform exercise during hospitalization. The purpose of this qualitative study was to understand exercise experiences in patients with metastatic lung cancer. Patients with metastatic lung cancer (n = 24) participated in face-to-face in-depth interviews at an inpatient ward of a medical center in central Taiwan. Interview transcripts were evaluated using narrative analysis to extract and validate themes. Three primary themes were identified: (1) modifying exercise to maximize physical functions; (2) living with symptoms and frustration, but still exercising; and (3) doing exercise to sustain hopes, inner power, and life. Secondary findings included: (1) adopting walking as their main form of exercise because of its convenience; and (2) among patients with severe symptoms, adjusting exercise towards shorter time durations and shorter distances, slower speeds, and higher frequencies. The study found physically active lung cancer patients, although with metastatic condition, adjusted their exercise activities to balance disease and treatment-induced deteriorations and boost themselves to feel hope and fight for cancer. However, the results may not be applicable to physically inactive patients. Future research to explore experiences from those with even worse physical conditions and further helping them to take some mild exercise to enhance the positive side of cancer experiences are suggested.